2017
DOI: 10.22175/mmb2016.12.0007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profile Differences between Beef Longissimus and Psoas Muscles during Display

Abstract: Abstract:The objective of this research was to compare metabolite profiles between beef longissimus and psoas muscles during display. Beef short loins were collected 3 d postmortem (n = 10). Steaks were cut from each longissimus lumborum (LL) and psoas major (PM) muscle and displayed under retail conditions for 7 d. Surface color, biochemical properties, and metabolites were analyzed during storage. PM decreased in redness (P < 0.05) by d 3 of display compared with LL. There were differences in metabolite conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Differences in whole steak surface oxygen consumption and nitric oxide metmyoglobin reducing activity between color‐stable and color‐labile muscles during display also have been documented (McKenna et al., ). In addition, the influence of sarcoplasmic proteome and metabolome on the differential color stability of beef LL and PM have been reported (Joseph, Suman, Rentfrow, Li, & Beach, ; Abraham, Dillwith, Mafi, VanOverbeke, and Ramanathan, ). However, no previous research has examined the role of mitochondrial functionality in muscle‐dependent color stability.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in whole steak surface oxygen consumption and nitric oxide metmyoglobin reducing activity between color‐stable and color‐labile muscles during display also have been documented (McKenna et al., ). In addition, the influence of sarcoplasmic proteome and metabolome on the differential color stability of beef LL and PM have been reported (Joseph, Suman, Rentfrow, Li, & Beach, ; Abraham, Dillwith, Mafi, VanOverbeke, and Ramanathan, ). However, no previous research has examined the role of mitochondrial functionality in muscle‐dependent color stability.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐five metabolites were identified in the 1 H NMR spectra; they were 10 amino acids (isoleucine, leucine, valine, alanine, glutamate, pyroglutamate, glycine, tyrosine, histidine, and phenylalanine), 2 sugars (glucose and sucrose), 1 alcohol (2,3‐butanediol), 4 organic acids (lactate, acetate, succinate, and creatine), 4 nucleotide metabolites (hypoxanthin, inosine, AMP, and 5′‐IMP), and 4 other metabolites (carnitine, histamine, nicotinamide, and creatinine). Metabolites such as isoleucine, leucine, glutamate, hypoxanthine, and inosine have been reported in fresh beef (Abraham, Dillwith, Mafi, Vanoverbeke, & Ramanathan, 2017; David, Juan Manuel, Rosa, Antonio, & María Isabel, 2015). However, metabolites like histamine, 2,3‐butanediol, and pyroglutamate were rarely detected before.…”
Section: Resultsmentioning
confidence: 99%
“…Post-mortem bovine mitochondria can use pyruvate for oxygen consumption . Abraham et al (2017) observed that the intensity of pyruvic acid in colour-stable beef LL was three times more than that in colour-labile psoas major. The low abundance of pyruvate dehydrogenase in the VITE group may result in lower conversion of pyruvate into acetyl-CoA so that more pyruvate could remain in post-mortem skeletal muscles resulting in an improved beef colour stability.…”
Section: Figurementioning
confidence: 93%